Pembelajaran Kaya Literasi dan Numerasi: Pendampingan Guru SD dalam Mendesain Pembelajaran Inovatif - Laksana, Dek Ngurah Laba; Lawe, Yosefina Uge; Elisantinia Endu (LPPM Universitas HKBP Nommensen, 2024)
The literacy and numerical learning outcomes of Golewa District primary school pupils were found to be in a very good category. In order to move these learning outcomes into the good category, support for elementary school teachers is needed to improve these results. Initiating learning that is rich in literacy and numeracy through mentoring activities in the development of creative learning designs for elementary school teachers in the Golewa District is one of the many efforts that need to be made. Training and lectures were used to carry out this work. Following data collection, a descriptive analysis was conducted to characterise the growth in teachers' knowledge and proficiency in creating lessons that are dense with numeracy and literacy material. Based on the actions that have been carried out, it can be concluded that the teacher's understanding of the concepts of literacy and numeracy is good. Apart from that, teachers have the skills to design learning that is multiple in literacy and numeracy for innovative learning.